The Persecution of French Jesuits by the Parlement of Paris 1761–71 - Thompson, D. Gillian (Studies in church history, 1984)
In the 1760s the parlement of Paris undertook to destroy the Society of Jesus in the central one-third of France which it controlled, and to use its influence to gain the destruction of the order elsewhere. Its immediate victims were the 1,200 Jesuits resident in 42 colleges and other institutions in its own territory in 1761, but it also claimed authority over any of the other 2,200 French Jesuits who had been born in its territory or might enter it. By this time four French Jesuits in five were priests or future priests whose primary functions were preaching and teaching; the remaining one in five was a temporal coadjutor, often an administrator of property. This ratio prevailed in the groups with whom the parlement dealt. The parlement viewed all Jesuits as enemies and regarded as a Jesuit any man who had ever made vows in that order. Then, as now, members of the Society of Jesus not only made the usual three religious vows but also owed complete obedience to their superior-general in Rome and were bound by the special vow of obedience to the sovereign pontiff taken by the professed of the order. The unique nature of the Jesuit institute was widely understood in France in the 1760s and was a reason for the respect shown to Jesuits by the privileged classes from which many Jesuits came and which they served so well.